Pengembangan Media Pembelajaran Berbasis Android Pada Mata Pelajaran Al-Qur’an Hadits Madrasah Aliyah - Neli Mu'minatin; Zarkasi, Zarkasi (LP2M Universitas Islam Ahmad Dahlan, 2023)
This study aims to determine the feasibility and effectiveness of learning media to increase student motivation, interest and learning outcomes. This research was conducted at MAN Pekalongan because the learning activities carried out at the madrasa, especially for the Al-Qur'an Hadith class X, some of them still used traditional methods and some of them used media but were limited to Microsoft PowerPoint so that it still seemed less effective. This type of research uses research and development methods (Research and Development) with the Addie development model. The samples taken were class X students of the Department of Science and Social Sciences at Madrasah Aliyah Negeri (MAN) Pekalongan. The data used is the value of the results of the pre test and post test then analyzed using the t test. The results of the study show that the android-based learning media used has a high level of effectiveness or success. High increase in interest and motivation results in high student learning outcomes as well, this is indicated by the average score of students' test results increasing 88% from 45.67 to 86.